EVALUASI PEMBANGUNAN FISIK KAWASAN PARIWISATA LOVINA DI KABUPATEN BULELENG - Nyoman Danendra Putra; Pradna Lagatama (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2020)
Physical development in the Lovina Tourism Area has several impacts, so it is necessary to conduct an evaluation of the development in the Lovina Tourism Area. Problems that arise regarding: 1) Impact arising from physical development; 2) Development of the Lovina Tourism Area is evaluated from a physical aspect. The research objective is to evaluate the physical development in the Lovina Tourism Area in Buleleng Regency towards sustainable tourism. Data were collected through group discussions, observations, and interviews. Sampling through group discussion (group discussion) and interviews. In analyzing the problems and research results, quantitative descriptive analysis was used. The results showed that the physical development in the Lovina Tourism Area had an impact on the Lovina Tourism Area, including: Physical impact, namely the proliferation of buildings as a means of tourism which resulted in excess supply, changes in beach cleanliness conditions, poorly maintained condition of tourism facilities; Social impact, namely changes in community behavior that mimic external cultural behavior, increased unemployment; The cultural impact, namely changes in traditional ceremonial facilities, decreased mutual cooperation and reduced artistic activities. The evaluations that have been carried out include: Physical aspects, namely the conversion of agricultural land to tourism land, less optimal public facilities to support tourism, not optimal waste or waste management, and violations of party boundaries; Social aspects, namely changes in the behavior of the people who tend to imitate foreign cultures, as well as shifting market segments from foreign tourists to domestic tourists; Cultural aspects, namely the decline in mutual cooperation activities, the decline in artistic activities, the erosion of the subak organization due to the narrowing of agricultural land. The government is expected to organize tourism facilities to create an attraction for the Lovina Tourism Area towards sustainable tourism and in accordance with the new life order.